Territorios indígenas, gobernanza y comunidades nativas en la Amazonía peruana: posibilidades y limitaciones - Chirif Tirado, José Alberto Carlos (2023)
Amazonian indigenous peoples in Peru are not well known. The prejudiced approach of Peruvian society prevents a thorough comprehension of these societies and denies their contributions to different domains of knowledge and their adaptation strategies to the amazon environment. This evidently has historical reasons. This investigation contributes to a better understanding of these societies, their conceptions regarding territory and their governance systems, and above all, to the explanation of the historical processes they have endured until they became native communities. Our specific goals are to explain their conceptions and traditional practices regarding territory and governance, the analysis of the historical transformations experimented by indigenous societies and the examination of new territorial and governance proposals. We have used a descriptive non-experimental methodology that tries to establish the causal relations (conceptions and state policies) and effects (result of these policies). It is an expost facto retrospective research. We start by presenting the theoretical background that guides the research. We shall study the transit between the traditional conceptions about territory nd governance through the analysis of the colonization processes, which have occurred during the last five centuries. We have gathered the information from historical and anthropological studies; our own experience of more than 50 years of professional practice; conversations with colleagues and other specialists and semistructured interviews regarding the new proposals about territory and governance, developed by some indigenous organizations. The most important findings are the profound modifications experimented by indigenous societies, as well as their exceptional capacity to adapt to change and their vitality to analyse the present moment and design alternatives that will allow them to respond to the challenges which they confront.